Difference in the distribution of tumor‐infiltrating CD8+ T cells and FOXP3+ T cells between micronodular thymoma with lymphoid stroma and micronodular thymic carcinoma with lymphoid stroma. Issue 7 (5th April 2021) - Yagi, Haruna; Nakaguro, Masato; Ito, Masafumi; Okumura, Yuki; Takahashi, Seishiro; Aoshima, Yoichiro; Enomoto, Yasunori; Meguro, Shiori; Kawasaki, Hideya; Kosugi, Isao; Shimoyama, Yoshie; Ogawa, Hiroshi; et al.
Abstract : Micronodular thymoma with lymphoid stroma (MNT) is a rare thymic epithelial neoplasm subtype characterized by a micronodular tumor cell growth pattern and abundant lymphoid stroma. Micronodular thymic carcinoma with lymphoid stroma (MNCA) is considered as a malignant counterpart of MNT and exhibits a growth pattern similar to that of MNT but has histologic features reminiscent of thymic squamous cell carcinoma, such as cytologic atypia and CD5 and CD117 immunoexpression. Although both MNT and MNCA are characterized by abundant lymphoid stroma, it remains unknown whether there are differences in infiltrating lymphocytes between MNT and MNCA. We analyzed the immune microenvironment profile in eight MNT and three MNCA cases. The cell density of CD8‐positive T cells was significantly higher in MNT than in MNCA, whereas that of FOXP3‐positive T cells was significantly higher in MNCA than in MNT. There was no significant difference in the cell density of programmed death protein 1‐positive T cells and programmed death ligand 1 expression between the MNT and MNCA cases. Our findings indicated that the immune microenvironment of MNCA differed from that of MNT and, compared with the T‐cell profile of MNT, that of MNCA was more suppressive to patients′ antitumor immune response.